Delivering Reality Therapy through Online Psychological Assistance for Healthcare workers during COVID-19 Pandemics - A.S, Nur Azizah; Algristian, Hafid; Khamida, Khamida; Ayu, Friska; Khairul Bariyah, Khadijah (UNUSA Press, 2025)
Introduction: Indonesia faces a critical situation with 8% of its COVID-19 deaths being healthcare workers (HCWs). These workers are highly susceptible to the virus due to contact with infected patients. Approximately 35.5% of HCWs treating COVID-19 patients develop symptoms within 14 days, and 7% test positive via PCR. Alarmingly, 36% of HCWs are asymptomatic, posing a significant risk of unknowingly spreading the virus. The pandemic has induced fear of death, infection, and transmitting the virus to family members among HCWs, necessitating psychological support to prevent burnout and maintain a functional healthcare system. Objective: This study aims to analyze the effectiveness of online psychological assistance for HCWs at the forefront of the COVID-19 battle. Methods: One of the psychological assistance methods offered is through social media applications. This type of psychological assistance can be considered the most practical and safe method because it prevents transmission between medical personnel. Results: The increasing number of COVID-19 patients has increased fatigue and infection rates among HCWs. They face uncertainty and feelings of loneliness during the pandemic. However, social support is crucial for psychological first aid and recovery. Misconceptions about COVID-19 being a conspiracy hinder HCWs' efforts. Promoting healthy behaviors such as hygiene practices and mask usage can mitigate the severity of the virus and improve survival rates. Conclusions: In 2020, the surge in COVID-19 cases has forced HCWs to adapt. Nonetheless, conspiracy theories about COVID-19 complicate their duties. Implementing an online psychological assistance application is essential to provide HCWs with the psychological support needed to adapt more effectively to the pandemic's challenges.